2007
DOI: 10.1101/gr.6687808
|View full text |Cite
|
Sign up to set email alerts
|

Controlled exchange of chromosomal arms reveals principles driving telomere interactions in yeast

Abstract: The 32 telomeres in the budding yeast genome cluster in three to seven perinuclear foci. Although individual telomeres and telomeric foci are in constant motion, preferential juxtaposition of some telomeres has been scored. To examine the principles that guide such long-range interactions, we differentially tagged pairs of chromosome ends and developed an automated three-dimensional measuring tool that determines distances between two telomeres. In yeast, all chromosomal ends terminate in TG 1-3 and middle rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 50 publications
11
96
1
Order By: Relevance
“…This organization largely favours interaction between centromeric proximal sequences as well as contact between subtelomeres (Bystricky et al 2005;Schober et al 2008;Therizols et al 2010;Duan et al 2010;Agmon et al 2013). Consistently, recombination between centromeres on one hand and between subtelomeric sequences on the other hand occurs efficiently (Burgess and Kleckner 1999;Brown et al 2010;Agmon et al 2013;Lee et al 2016).…”
Section: Finding a Homologous Sequence Is A Challenge In The Nuclear mentioning
confidence: 64%
“…This organization largely favours interaction between centromeric proximal sequences as well as contact between subtelomeres (Bystricky et al 2005;Schober et al 2008;Therizols et al 2010;Duan et al 2010;Agmon et al 2013). Consistently, recombination between centromeres on one hand and between subtelomeric sequences on the other hand occurs efficiently (Burgess and Kleckner 1999;Brown et al 2010;Agmon et al 2013;Lee et al 2016).…”
Section: Finding a Homologous Sequence Is A Challenge In The Nuclear mentioning
confidence: 64%
“…These single structures have been used to make inferences about the organization of the respective genomes. 6,9 Microscopic studies show considerable variation in the distances between pairs of loci within populations of cells 10,11,13 and…”
Section: Resultsmentioning
confidence: 99%
“…6,8,9 These studies resulted in the proposal of unique genome conformations that do not represent the dynamic nature of nuclear organization. However, it is important to incorporate dynamism because genome organization shows a lot of variability [10][11][12] indicating that it must change from cell to cell and over time. Critically, the chromosomal interactions identified by proximity-based ligation are averaged across the test cell population and the subset of interactions that is present in a single cell cannot be determined.…”
Section: Chromosome Positioning and The Clustering Of Functionally Rementioning
confidence: 99%
“…Structural data obtained by statistical positioning of a gene in a yeast cell population led to a surprisingly simple model to define yeast nuclear architecture (Zimmer and Fabre 2011): Chromosome position can be predicted by a few parameters such as genomic arm length, telomeres (TEL), and centromeres (CEN) tethered to the NE via nuclear-envelope-tethered proteins and to the SPB via microtubules, respectively (Bystricky et al 2005;Therizols et al 2010;Zimmer and Fabre 2011). This description was recently complemented by the first Hi-C comprehensive maps (Rodley et al 2009;Duan et al 2010), which confirmed an organization guided by nuclear landmarks, including TEL that congregate in foci (Gotta et al 1996;Schober et al 2008). Recent Brownian dynamics (BD) simulations confirmed this structural model by recapitulating Hi-C and imaging data, assuming that physical tethering at TEL and CEN and volume exclusion were driving chromosome conformations (Tjong et al 2012;Wong et al 2012).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 89%